2006
DOI: 10.1021/jm0606342
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridyl Thiosemicarbazone Chelators with Potent and Selective Antitumor Activity Form Iron Complexes with Redox Activity

Abstract: Table S1. Crystal data and structure refinement for HDp4mT. Identification code ds2369 Empirical formula C 13 H 13 N 5 S Formula weight 271.34 Temperature 293(2) K Wavelength 0.71073 Å Crystal system Monoclinic Space group C2/c Unit cell dimensions a = 19.740(2) Å α= 90°. b = 11.694(1) Å β= 91.391(9)°. c = 11.514(2) Å γ = 90°. Volume 2657.1(6) Å 3 Z 8 Density (calculated) 1.357 Mg/m 3 Absorption coefficient 0.237 mm -1 F(000) 1136 Crystal size 0.5 x 0.5 x 0.3 mm 3 Theta range for data collection 2.02 to 24.96°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
644
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 356 publications
(714 citation statements)
references
References 66 publications
68
644
2
Order By: Relevance
“…Considering this finding, we suggest that it is the effect of the chelator entering the cancer cell, binding Fe, and forming the cytotoxic Fe complex (10,26) that leads to its antitumor activity. In fact, we have shown that the antitumor efficacy of the DpT chelators is proportional to their effective redox activity (26).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Considering this finding, we suggest that it is the effect of the chelator entering the cancer cell, binding Fe, and forming the cytotoxic Fe complex (10,26) that leads to its antitumor activity. In fact, we have shown that the antitumor efficacy of the DpT chelators is proportional to their effective redox activity (26).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, upon PKIH and DpT ligands forming Fe complexes, these ligands generate cytotoxic ROS (10,(26)(27)(28). The resulting oxidative damage potentiates the antiproliferative activity of PKIH and DpT chelators compared with 2-hydroxy-1-naphthylaldehyde isonicotinoyl hydrazone or DFO, which bind Fe but do not redox cycle (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current understanding of the structure activity relationship of MDR selective isatin-β-TSCs suggests a beneficial effect of an aromatic moiety at N4 [21,39]. Similarly, introduction of a phenyl substituent to the N4 position has been shown to increase the toxicity of dipyridylketone TSCs to a comparable extent as terminal dimethylation [23,47]. In contrast to Dp44mT and NSC73306, the toxicity of the terminally unsubstituted NNS thiosemicarbazone Triapine is attenuated by P-gp [20,21,48].…”
Section: Design and Synthesis Of A Focused Chelator Librarymentioning
confidence: 99%